Efficacy and cost-effectiveness of phenotyping for rice resistance and tolerance to planthoppers - Horgan, Finbarr G.; Mundaca, Enrique A.; Quintana, Reyeul; Naredo, Alberto I.; Almazan, Maria Liberty P.; Bernal, Carmencita C. (MDPI, 2021)
The standard seedling seedbox test (SSST) is the most prevalent phenotyping test in research on the genetics and breeding of planthopper-resistant rice. Using 16 rice lines that included plants susceptible, resistant and tolerant to the brown planthopper (Nilaparvata lugens), we compared the SSST to modified seedling seedbox tests (MSSTs) and the days-to-wilt (DTW) test. We also conducted a series of performance tests to assess nymph survival and development; adult longevity and egg-laying; egg survival; honeydew production; and plant weight loss. We also assessed the relative costs of the different phenotyping tests to better recommend test protocols that are suitable for high-throughput phenotyping. The SSST was found to be highly robust but fails to identify late-stage resistance; tolerance; or ovicidal responses. MSSTs improved phenotyping by identifying plants with low damage from planthoppers at later growth stages. Herbivore performance tests such as population or biomass build-up tests reduce space requirements and reduce setup and evaluation costs compared with bulk tests. They can also facilitate the assessment of plant tolerance; albeit with added costs. The DTW test most clearly segregates resistant and susceptible plants, thereby facilitating gene discovery and marker-assisted selection. We recommend that bulk testing be improved by switching from the SSST to a suitable MSST and that donor variety and pre-release lines be assessed for the nature of rice–planthopper interactions using biomass build-up tests—including the DTW test.